Brain structural correlates of depressive symptoms in Parkinson's disease patients at different disease stage. (29th February 2020) - Li, Yanxuan; Huang, Peiyu; Guo, Tao; Guan, Xiaojun; Gao, Ting; Sheng, Wenshuang; Zhou, Cheng; Wu, Jingjing; Song, Zhe; Xuan, Min; Gu, Quanquan; Xu, Xiaojun; et al.
Highlights: Depression occurs frequently in Parkinson's disease (PD) patients. Lewy body accumulation can damage emotion circuit and cause depression. We studied brain structural correlates of depression in PD at early and middle stages. Depressive symptoms in middle stage PD were more related to gray matter changes. The neural basis of depression may be distinct in PD patients at different stages. Abstract: Parkinson's disease (PD) pathology may damage emotion circuit and cause depression. We investigated whether the neural basis of depressive symptoms varies at different PD stages. Seventy-six healthy controls (HC) and 98 PD patients (divided into early and middle stage groups) underwent brain magnetic resonance imaging (MRI) and general neuropsychological tests. Voxel-based morphometry and tract-based analysis were used to study the association between brain structural alterations and the Hamilton Depression Scale 17 Item (HAMD-17) scores in different groups. Comparing with HC group, PD patients showed widespread brain alterations in both gray and white matter. The HAMD-17 scores were positively correlated with GM volume in the right pre-central gyrus of early PD patients. In the middle stage group, HAMD-17 scores were positively correlated with GM volume in midbrain and right superior temporal gyrus, and negatively associated with GM volume in left anterior cingulate and superior frontal gyrus. In white matter analysis, The HAMD-17 scores were positively correlated with fractional anisotropy value of the bilateral inferior fronto-occipital fasciculus in the early stage group, but not the middle stage group. We concluded that the neural basis of depressive symptoms might be distinct in different stages of PD, implying the need for differential treatments.